2017
DOI: 10.1002/ajhb.23013
|View full text |Cite
|
Sign up to set email alerts
|

Body fat attenuates muscle mass catabolism among physically active humans in temperate and cold high altitude environments

Abstract: These results suggests that during a negative energy balance dietary macronutrient content cannot abate the loss of muscle mass, but body fat may have a protective effect. This information should be used to improve individualized diets based on body composition, not body mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 41 publications
1
20
1
Order By: Relevance
“…Although most studies indicate favourable physiological and physical changes in increasing athletes' performance, altitude training also has negative effects such as a decrease in body weight (in the present study by 2.1%) [41][42][43][44]. However, no such differences were observed in the current study after training on the sand.…”
Section: Haemoglobin Concentrationscontrasting
confidence: 78%
“…Although most studies indicate favourable physiological and physical changes in increasing athletes' performance, altitude training also has negative effects such as a decrease in body weight (in the present study by 2.1%) [41][42][43][44]. However, no such differences were observed in the current study after training on the sand.…”
Section: Haemoglobin Concentrationscontrasting
confidence: 78%
“…The MM in the one study that involved passive exposure remained unchanged (ET: 7 days) (Lippl et al, 2010). A significant reduction in MM of -1.5 kg was observed in male participants and an increase of 0.6 kg in female participants that had a prolonged active exposure to cold climate conditions (ET: 112 days) (Ocobock, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Significant losses of FFM and MM were observed at altitudes as low as ≤5000 m (Ocobock, 2017), with the extent dependent on duration, temperature and body fat percentage at the outset. These results were confirmed in a very recent study that showed that there is muscle wasting even during short simulated exposures (21 days) to an altitude of only 4000 m under strictly controlled and standardized environmental, dietary and activity conditions (Debevec et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work among highly active humans in a variety of natural environments revealed high TEE sustained over three to four months (Ocobock 2016a, 2016b, 2017). Subjects in this study took part in a variety of physical activities ranging in type and intensity and did so in temperate and cold environments.…”
Section: New Theories Regarding Human Energy Expenditurementioning
confidence: 99%